Behavior model of knowledge, attitude, and skills in practicing safety and health in the workplace among higher education engineering students - Shaari, Nabilah Hasanah; Mohd Puad, Mohd Hazwan (Human Resources Management Academic Research Society (HRMARS), 2023)
Safety and health practices are essential to avoid the risk of accidents in the work environment. They help mitigate unsafe behaviors, create a safe work environment, prevent accidents, and improve organizational performance. By prioritizing safety and health, organizations, including higher education institutions, can protect their employees, customers, and students and enhance overall productivity. Minimizing the risk of accidents and promoting safety practices requires a comprehensive understanding of the knowledge, attitude, and skills of professionals and workers. Several studies have explored these factors in different workplace settings. This study examines the level of knowledge, attitude, and skill in practicing safety and health in the workplace and its relationships among higher education engineering students. This study used a quantitative and correlational design. The researchers utilized a questionnaire survey instrument of 33 items on 248 respondents from a random sampling of final-year engineering students at Malaysian higher education institutions. The collected data were analyzed by using IBM SPSS Statistics software. The results showed that the knowledge, attitude, and skill level in safety and health practices are high and satisfactory. Significant positive relationships existed among the safety and health practices variables among higher education students. This study confirms the role of behavior models, knowledge, attitude, and skills in culturing safety and health practices in the workplace. This study will benefit those involved in improving safety and health practices in the laboratory of higher education institutions or real-work settings.